Breakdown of the central synapses in C9orf72-linked ALS/FTD - Ghaffari, Layla T.; Trotti, Davide; Haeusler, Aaron R.; Jensen, Brigid K. (Frontiers in Molecular Neuroscience, 2022)
Amyotrophic lateral sclerosis (ALS) is a progressive, fatal neurodegenerative disease that leads to the death of motor and cortical neurons. The clinical manifestations of ALS are heterogenous, and efficacious treatments to significantly slow the progression of the disease are lacking. Cortical hyper-excitability is observed pre-symptomatically across disease-causative genetic variants, as well as in the early stages of sporadic ALS, and typically precedes motor neuron involvement and overt neurodegeneration. The causes of cortical hyper-excitability are not yet fully understood but is mainly agreed to be an early event. The identification of the nucleotide repeat expansion (GGGGCC)n in the C9ORF72 gene has provided evidence that ALS and another neurodegenerative disease, frontotemporal dementia (FTD), are part of a disease spectrum with common genetic origins. ALS and FTD are diseases in which synaptic dysfunction is reported throughout disease onset and stages of progression. It has become apparent that ALS/FTD-causative genes, such as C9ORF72, may have roles in maintaining the normal physiology of the synapse, as mutations in these genes often manifest in synaptic dysfunction. Here we review the dysfunctions of the central nervous system synapses associated with the nucleotide repeat expansion in C9ORF72 observed in patients, organismal, and cellular models of ALS and FTD.